Pembelajaran Bahasa Indonesia Daring Berbasis Gawai “Quizizz” pada Era Kelimpahan - Randi Ramliyana; Vickry Ramdhan (SAP (Susunan Artikel Pendidikan), 2021)
In the current era of abundance, all learning activities have shifted to online, one of which is learning Bahasa at universities. Bahasa learning in universities discusses writing scientific papers. This writing is intended for sixth semester students in preparing themselves to write a thesis/final project. Meanwhile, writing scientific papers requires a lot of practice in writing so that it requires appropriate learning media in the current era of abundance. Therefore, the Quizizz device-based application was chosen as an online Bahasa learning medium. This study aims to describe the application of Quizizz as an online Bahasa learning medium. The application of Quizizz in Bahasa classes has made learning situations both fun and challenging. Quizizz is packaged in learning as part of the learning material. Learning using Quizizz not only explains the material being taught, but also evaluates students' understanding and skills in absorbing the material presented in the form of slides and evaluations that are fun and can be done anywhere. This paper is a literature review that explores from various library sources, both books and journals. This paper shows that Quizizz can produce creative, innovative, and fun learning media so that it needs to be applied as a learning medium in the current era of abundance.